Influence Use Media Based Canva On Learning Outcomes Of Citizenship Education Class Xi Students Of Private Senior High School (SMAS) Muhammadiyah Pangsid - Hikmah D, Nur; Syamsunir, Syamsunir; M, Usman; Hermansyah, Sam (International Journal of Language and Ubiquitous Learning, 2023)
Background. Based on the results of observations at Private Senior High School Muhammadiyah Pangsid, researchers saw that teachers still used the lecture method in the learning process with voices that were not clear during the learning process. And media which used Still depend on book package Which less interesting so students feel bored and cannot concentrate on what the teacher is saying. With Canva- based media , it is hoped that it can help the teaching and learning process can be implemented well. Purpose. The research focuses on Canva as a presentation-based learning tool with diverse templates to boost student interest in the material. Observations at Private Senior High School Muhammadiyah Pangsid revealed a concern: low student interest affecting learning quality and school credibility. Addressing this issue is crucial for enhancing overall educational outcomes.Top of Form. Method. The research This research uses an experimental type of research. Sugiyono explained that "Method study experiment can  interpreted as research methods used to find the effect of certain   treatments towards others in controlled conditions” (Anggoro, 2016). Results. The results of the experimental group that used Canva- based media in the learning process obtained higher scores compared to the group control Which No using media based canva on moment learning process. Matter the can seen from the results acquisition analysis that data carried out shows the average value of the experimental group. Conclusion. Research on the impact of Canva in teaching Citizenship Education to Class XI at Private Senior High School Muhammadiyah Pangsid shows positive results. With an average score of 83.214, significantly higher than the control group's 65, and a t-test result of 8.204 exceeding the critical value, Canva positively influences Citizenship Education outcomes.